Screening of Peripheral Arterial Disease in Patients with Diabetes - Ghimire, Mahesh Raj; Acharya, Sumnima; Pandey, Sundar; Aryal, Deepak; Shah, Pooja; Soti, Binita; Ghimire, Sulochana; Thapa, Lekhjung (Journal of Nepal Health Research Council, 2023)
Background: Out of many atherosclerotic complications, peripheral arterial disease (PAD) is also important one. To prevent morbidity and mortality related with PAD, early detection is must, and is possible by duplex screening. This study aims at screening for PAD in patients with type 2 Diabetes mellitus.Methods: This study is single centered cross- sectional, observational study conducted in department of internal medicine of DMCRI- a tertiary care hospital. A total of 140, type 2 diabetes patients were screened for peripheral arterial disease by duplex ultrasound after taking informed consent and fulfilling inclusion and exclusion criteria.Results: In our study among 140 Participants, 50% are male and 50% are female with mean age of 57.6 ± 10.4 years standard deviation (SD) and mean duration of diabetes was 8.31± 5.9 SD years with 13.6% were alcohol consumer; 1.4% were smokers; 59.3% of them had high blood pressure; (28.6%) had dyslipidaemia and 11.4% had hypothyroidism. The prevalence of PAD in type 2 diabetes was 27.1% in our study. The mean of glycated hemoglobin (HBA1c) was 7.23 ± 1.75% and while performing analytical test {chi-square (?)}, we found there was no association between HBA1c level and presence of peripheral arterial disease.Conclusions: The prevalence of peripheral arterial disease is high almost more than one quarter (27.1%). Screening of diabetic patients is must especially those aged and high glycated hemoglobin for early detection and effective management of PAD. Keywords: Diabetes mellitus; glycated hemoglobin; peripheral arterial disease; screening